From Jesus to the Gospel of Mark: The way of tradition - Riesner, Rainer (Vox Scripturae - Revista Teológica Internacional, 2014)
The cultivation of a tradition surrounding Jesus already initiated before Easter. Jesus himself impregnated his words in his disciple in such a way that they were easy to be kept in memory. Right after Easter, Peter and other disciples also transmitted forward, in the same way, the actions of Jesus. Mark was, since the first years of Jerusalem’s primitive community, in contact with Peter. Already before the publication of his gospel, which could have occurred early, in 64/65, in any case, before 70, Mark preserved written traditions about Jesus. The Gospel of Mark, for this, deserves trust as a reliable account on the person and the work of Jesus.
Keywords: Tradition on Jesus; Gospel of Mark; Peter and Mark